Doença pneumocócica invasiva em crianças e adolescentes soropositivos para HIV - Mattei, Sonia M. (2008)
OBJECTIVE: Invasive pneumococcal disease (IPD) primarily affects children less than 5 years old, the elderly and certain at-risk groups; especially people infected by the human immunodeficiency virus (HIV). The objective of this study was to analyze invasive pneumococcal diseases (IPD) in children and adolescents infected by the human immunodeficiency virus (HIV), with relation to morbidity, the case fatality ratio, pneumococcus serotypes, susceptibility to penicillin and ceftriaxone and to the proportion of susceptible and resistant Streptococcus pneumoniae (Sp) included in the 7-valent pneumococcal conjugate vaccine that has already been licensed. METHODS: A total of 19 cases of IPD were identified among HIV seropositive patients aged from 1 month to 20 years and hospitalized between 1993 and 2000. Data were recorded on standardized charts containing information on age, clinical diagnosis and progression, serotypes and the susceptibility to penicillin and ceftriaxone of the Sp strains identified in cultures. When the minimum inhibitory concentration was < 0.1 mcg/mL, Sp were defined as susceptible to penicillin (SpSPn), and all other strains were defined as not susceptible (SpNSPn). RESULTS: Of the 19 HIV seropositive cases with IPD, 16 (84%) had pneumonia and three (16%), had meningitis; 13 (68%) cases were children less than 2 years old and 16 (84%) were less than 5 years old. The case fatality ratio was 10%. Seven (54%) of the 13 cases less than 2 years old were SpNSPn and 10 (77%) were caused by serotypes covered by the 7-valent pneumococcal conjugate vaccine. From the 10 isolated serotypes the most frequent were 14, 6B and 23F, all them susceptible to ceftriaxone. From the three patients with meningitis, two were caused by SpNSPn. CONCLUSION: In this study most of the IPD occurred in children less than 2 years old; 77% of the strains and 86% of the serotypes of SpNSPn were covered by the 7-valent pneumococcal conjugate vaccine.